(untitled) (Indian Journal of Animal Production and Management, 2024)
The present investigation was carried out to compare herd composition (buffaloes, cows, heifers, calves, breeding bull, total herd strength) and infrastructure facilities (assets and implements) of specialized dairy farms in north (n=10) and south (n=10) semi-arid to arid and medium to high rainfall agro-climatic zones respectively. In northern region higher mean average of cross-breed cattle (82.20 vs. 23.25, p=0.01) compared to southern region. Opposite to this in southern region higher mean average of buffalo (85.00 vs. 3.77, p=0.00) compared to northern region. Whereas in southern region slightly higher mean average of total herd strength (111.70 vs. 86.60, p=0.11) compared to northern region. The facility of infrastructure in both region possessed similar proportion of average adult animal shed, individual calf shed, pregnant animal shed, sick animal shed. Store-dutch barn, milking parlour, feed factory, labour house, milk storage room, staff office, tractor, hydraulic trailer, mannual as well as electric chaff cutter, shredder, water pipe router, dung scraper, automatic grooming brush, bulk milk cooler, milking parlour, deep freezer, automatic ghee maker and milk packaging machine. However, Northern region had higher proportion of milking machine (80% vs. 20%, p=0.00) as compare to southern region. Present study indicated that herd composition differed between two regions might be attributed to climatic difference including moisture and rainfall pattern along with marketing pattern.